Out of hours workload management: Bayesian inference for decision support in secondary care - Pérez López, Iker; Brown, Michael; Pinchin, James; Martindale, Sarah; Sharples, Sarah; Shaw, Dominick E.; Blakey, John (Elsevier, 2016)
Objective: In this paper, we aim to evaluate the use of electronic technologies in Out of Hours (OoH) task-management for assisting the design of effective support systems in health care; targeting local facilities, wards or specific working groups. In addition, we seek to draw and validate conclusions with relevance to a frequently revised service, subject to increasing pressures.